The Effect of Rewards, Punishments, and Organizational Culture on the Performance of Marketing Financing Employees at PT Bank Syariah Indonesia Regional 3 Palembang - Juhendra, Muhammad; Karimudin, Yos; Cahyadi, Afriyadi; Muhammad Ichsan Hadjri; Zunaidah (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This study aims to empirically examine the effects of rewards, punishments, and organizational culture on the performance of marketing financing employees at PT Bank Syariah Indonesia (BSI) Regional 3 Palembang. A quantitative research design was employed using a survey method involving 238 respondents from the marketing financing division. Data were analyzed using multiple linear regression to evaluate both the simultaneous and partial effects of the independent variables rewards, punishments, and organizational culture on employee performance.The results show that rewards, punishments, and organizational culture each have a positive and significant impact on employee performance. These findings highlight the importance of implementing proper reward systems, fair punishment policies, and cultivating a strong organizational culture to improve employee performance. However, the three variables collectively explain only 20.3% of the variance in employee performance, suggesting that 79.7% may be influenced by other factors not examined in this study. This study contributes to the literature on human resource management in the Islamic banking sector by integrating Goal Setting Theory to explain how performance-based incentives and cultural alignment shape employee behavior. The practical implications can guide BSI leadership in designing more targeted HR strategies to enhance competitiveness and productivity.